Transferring Benefits and Damages in Certain Bequeathed Property (Art. 518/I of the Turkish Civil Code) - Merve Ürem Çetinel (İstanbul Hukuk Mecmuası)
The study takes the transfer of benefits and damages in regards regard to a specific endowment, which is defined in Art. 517/I of the Turkish Civil Code as the disposition of property to a person without them being made an heir per se, as the subject of analysis due to its importance. Art. 518/I of the Turkish Civil Code stipulates that bequeathed property must be delivered to the beneficiary in its current state once succession has begun, and the benefits and damages associated with this property will also pass on to the beneficiary at this time. In light of this distinction, this paper study will focus on legacies, specifically in regard to the changes that occur to the bequeathed property before and after the start of succession. The study will also analyze demonstrative legacy, procurement legacy, and conditional legacy as the types of legacies. The first part of this paper addresses the changes that happen to a bequeathed property up to the start of succession and the consequences of these changes. This part will examine the question of who will bear or benefit from the material and legal changes that have occurred up to the death of the testator. Meanwhile, the second part of the study will analyze the changes that occur to bequeathed property once succession has been initiated. According to Art. 518/I of the Turkish Civil Code, these changes are called benefits and damages. In light of this, defining benefit and damage as terms within the context of legacy and explaining what is meant by transferring benefits and damages in the context of legacy are important. However, the analysis will exclude the topic of expenditures made by those who are obliged to fulfill the requirements of the legacy regarding a bequeathed property.